Exploring southern African Plateau uplift with landscape evolution modelinversion and erosion history data - (:unkn) unknown (My University, 2017)
The southern African plateau is a dominant feature of African topography but there is considerable debate aboutwhen and how it formed. Cretaceous kimberlite activity and the presence of a large low shear seismic velocityprovince (LLSVP) in the deep mantle below southern Africa have lead many to propose uplift related to mantleprocesses. Better constraints on the timing of uplift have the potential to constrain the nature of the LLSVP andthe source of support for southern Africa’s anomalous elevations. However, surface uplift is difficult to detectdirectly in the geologic record and the relationships between mantle-sourced uplift and erosion are not necessarilydirect. Here, we use a landscape evolution model combined with data constraining the spatiotemporal erosionpatterns across southern Africa to explore how topographic development and erosion are related. This is an ideallocation to utilize this approach because several recent studies have helped to constrain the erosion history ofthis region over different spatial and temporal scales but the uplift history is still widely debated. We integrate ahighly efficient landscape evolution model (FastScape, Braun and Willett, 2013) and a thermal module with a largelow temperature thermochronology dataset, sedimentary flux volumes for the major offshore basins, and geologicobservations to address these questions. We used inversion methods based on the Neighborhood Algorithm toinvestigate how data is best simulated by the model while varying model parameters related to plateau uplift andthe physical characteristics of the eroding material. This is a powerful approach because we are able to comparemodel outputs to many aspects of topographic shape and constraints on the erosion history simultaneously. Resultsfrom the inversions show that the data are sufficient to constrain many model parameters. Additionally, we showthat the combination of different types of data, and in particular t
Keywords: African Research